2020
DOI: 10.1186/s43046-020-00054-0
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of hepatitis C virus infection in Egyptian multiple myeloma patients

Abstract: Background Multiple myeloma (MM) is a human B cell neoplasia characterized by the clonal proliferation of malignant plasma cells in the bone marrow. Worldwide, hepatitis C virus (HCV) infection is a public health problem. For MM patients, the clinical impact of preexisting HCV infection is still unclear. We aim to assess the clinical characteristics and the prevalence of the HCV infection in Egyptian MM patients. This observational study included 81 MM patients. HCV antibody assay was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Abnormal bilirubin levels and higher serum calcium levels were associated with higher HR of 7.04 and 10.9, respectively (with p-values of \<0.001 and 0.038, respectively) for disease-free survival in MM. 13 Similar findings were reported in the study by Nasr et al . (2021), in which the presence of hypercalcemia during diagnosis was associated with shorter progression-free survival (PFS) (unadjusted HR = 6.48; p\<0.008) and OS (unadjusted HR = 6.58; p\<0.006).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Abnormal bilirubin levels and higher serum calcium levels were associated with higher HR of 7.04 and 10.9, respectively (with p-values of \<0.001 and 0.038, respectively) for disease-free survival in MM. 13 Similar findings were reported in the study by Nasr et al . (2021), in which the presence of hypercalcemia during diagnosis was associated with shorter progression-free survival (PFS) (unadjusted HR = 6.48; p\<0.008) and OS (unadjusted HR = 6.58; p\<0.006).…”
Section: Resultssupporting
confidence: 88%
“… 1,14,18,19,23 Of the 10 studies in which patients were classified according to the International Staging System (ISS), five reported stage 3 (40.6%–53% of all MM cases) 1,12,18,21,24 whereas six reported that MM was most commonly diagnosed at stage 2 (41%–67%). 13,16,19,22,23 The male:female ratios ranged from 0.61 to 2.0 across all 14 reports. 14,24 Eleven studies enrolled newly diagnosed patients with MM.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This new approach should be useful for a significant fraction of MGUS and MM patients: for instance, a recent study revealed that until 7.4% of MM patients were positive for HCV RNA by RT-PCR assay. In this study, the authors emphasize that serologic tests at the time of diagnosis of MM are necessary to identify infected patients, and they propose that confirmation of positive cases by molecular techniques should be mandatory ( 29 ). Whether the gammapathy is linked to the infectious agent can then be addressed by showing that the patient’s monoclonal Ig reacts against the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…This work was supported by grants to SH from the Ligue Nationale contre le Cancer (Comiteś Deṕartementaux 44, 56, 29,85,35) and International Myeloma Foundation (IMF) (Brian D. Novis senior grant). We acknowledge the Instituto de Investigación Sanitaria Hospital 12 de Octubre (imas12), CIBERONC, AECC (Accelerator Award and Ideas Semilla), and the CRIS foundation for their help.…”
Section: Fundingmentioning
confidence: 99%